Dynamics of Transforming Growth Factor (TGF)-β Superfamily Cytokine Induction During HIV-1 Infection Are Distinct From Other Innate Cytokines - Dickinson, Matthew; Kliszczak, Anna E.; Giannoulatou, Eleni; Peppa, Dimitra; Pellegrino, Pierre; Williams, Ian; Drakesmith, Hal; Borrow, Persephone (Frontiers in Immunology, 2020)
Human immunodeficiency virus type 1 (HIV-1) infection triggers rapid induction of multiple innate cytokines including type I interferons, which play important roles in viral control and disease pathogenesis. The transforming growth factor (TGF)-β superfamily is a pleiotropic innate cytokine family, some members of which (activins and bone morphogenetic proteins (BMPs)) were recently demonstrated to exert antiviral activity against Zika and hepatitis B and C viruses but are poorly studied in HIV-1 infection. Here, we show that TGF-β1 is systemically induced with very rapid kinetics (as early as 1-4 days after viremic spread begins) in acute HIV-1 infection, likely due to release from platelets, and remains upregulated throughout infection. Contrastingly, no substantial systemic upregulation of activins A and B or BMP-2 was observed during acute infection, although plasma activin levels trended to be elevated during chronic infection. HIV-1 triggered production of type I interferons but not TGF-β superfamily cytokines from plasmacytoid dendritic cells (DCs) in vitro, putatively explaining their differing in vivo induction; whilst lipopolysaccharide (but not HIV-1) elicited activin A production from myeloid DCs. These findings underscore the need for better definition of the protective and pathogenic capacity of TGF-β superfamily cytokines, to enable appropriate modulation for therapeutic purposes.